Requirements for the Main Features of the Melted Cheese Products and Special Regulations - A. A., Samatov; N. S., Eshdavlatov (American Journal of Biology and Natural Sciences, 2025)
This article discusses requirements for the main features of the melted cheese products and special regulations. The demand for milk and dairy products, which is one of the most important products for the human body, is growing rapidly. As a result of continued competition in the production of milk and dairy products, the need to increase the new assortment of dairy products in our country. It is no coincidence that one of these products, melted cheeses, has become one of our favorite products today.